Complete genome sequences of pLMA1 and pLMA7, two large linear plasmids of Micrococcus strains isolated from a high-altitude lake in Argentina - Dib, Julian Rafael (2018)
The two linear plasmids pLMA1 (109,112 bp) and pLMA7 (82,075 bp) from Micrococcus strains were isolated from a high-altitude lake in the Argentinean Puna, sequenced, and annotated. These extrachromosomal elements are probably conjugative and harbor genes potentially involved in coping with the harsh conditions in such extreme environments.